Customer share of visits to full-service restaurants in response to perceived value and contingency variables - Kim, Wansoo (Kansas State University, 2009)
This study sought to apply the concepts of ‘perceived value’ and ‘customer share’ (of visits) to full-service restaurant settings for the first time. Given the strong ‘experiential nature’ of foodservice, the perceived value concept adopted in this study involved an ‘experiential view’ of the dining experience. Further, the customer share concept was expected to have implications for the foodservice context, given the multi-loyalty nature of restaurant customers. With the first conceptual model, this study sought to verify the effect of perceived value on customer share of visits in a full-service restaurant context, using a dimension-level value approach and positing customer satisfaction and brand preference as mediators between them. The conceptual model was tested based on responses from 299 general U.S. full-service restaurant customers, using a confirmatory factor analysis and structural equation modeling. The test results revealed that among four value dimensions, excellence (in food and service) and customer return on investment had dominant effects on customer satisfaction and brand preference whereas playfulness had a significant moderate effect only on brand preference; aesthetic appeals did not have significant effects on either. Affected by perceived value, customer satisfaction significantly enhanced brand preference and in turn brand preference contributed to customer share of visits and fully mediated the effect of customer satisfaction on customer share of visits. In essence, the findings highlight the significant antecedent role of perceived value in customers’ satisfaction and brand preference formation, and the pivotal role of customer brand preference in customers’ purchase decision process. With the second conceptual model, this study sought to reveal the direct effect and/or moderating effects of contingency variables in relation to customer share of visits in a fullservice restaurant context. The hypotheses included in the conceptual model were tested based on responses from 291 general U.S. full-service restaurant customers, using a confirmatory factor analysis and a series of (moderated hierarchical) regression analyses. The test results indicated that the direct effects of social switching costs, lost benefits costs, procedural costs, and intrinsic inertia were positive whereas that of intrinsic variety-seeking was negative on customer share of visits. In addition, consumer involvement and perceived brand heterogeneity were found to enhance the effect of brand preference on customer share of visits. The effects of the contingency variables appear to work by influencing the number of brands in customers’ consideration sets and/or leading customers to allocate a greater share of visits to a particular brand in a given number of brands in consideration sets.
Keywords: Perceived value; Customer satisfaction; Brand preference; Customer share of visits; Contingency variables; Full-service restaurant; Business Administration, Marketing (0338)